Disclosure and Lawsuits Ahead of Initial Public Offerings - Esmer, Burcu; Ozel, N. Bugra; Sridharan, Suhas A. (The Accounting Review, 2023)
ABSTRACT We examine whether initial public offering (IPO) registration disclosures expose firms to greater nonshareholder litigation risk. Using hand-collected data on lawsuits initiated at federal and state courts against IPO firms, we show that firms that submit their IPO registration statement with the Securities and Exchange Commission publicly experience a 16 percent increase in litigation risk between the registration filing and issuance date. Consistent with the public filing of the registration driving this heightened litigation risk, firms that file their registration confidentially under the Jumpstart Our Business Startups (JOBS) Act do not experience such an increase in litigation risk. The effects of confidential filing are concentrated among business-initiated lawsuits, intellectual property/contract lawsuits, and potentially meritless lawsuits. We find no disproportionate increase in lawsuits after an IPO for confidential filers, suggesting that withholding information during the IPO registration period mitigates litigation risk. JEL Classifications: G32; K20; K41; M41.